2015
DOI: 10.1099/jmm.0.000039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on the expression of Barrett’s oesophagus biomarkers

Abstract: Barrett's oesophagus (BO) is a complicated condition at the gastroesophageal junction in which normal squamous epithelium is changed to columnar and leads to oesophageal adenocarcinoma (OA). In the past decades, the prevalence of Barrett's disease and mortality rate of adenocarcinoma has significantly increased throughout the word. Data has shown that molecular pathogenesis of disease has not been clearly identified. However, a wide-range and successful administration of probiotics in cancer and gastrointestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Bacteria were then centrifuged (2500 × g, 25 minutes), washed once by PBS, counted in haemocytometer and resuspended to concentration of 3 × 107 ml −1 . S. salivarius was grown aerobically in WC broth at 37°C for use as a negative control, as part of the normal human oesophageal microbiota ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria were then centrifuged (2500 × g, 25 minutes), washed once by PBS, counted in haemocytometer and resuspended to concentration of 3 × 107 ml −1 . S. salivarius was grown aerobically in WC broth at 37°C for use as a negative control, as part of the normal human oesophageal microbiota ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Barrett’s associated adenocarcinoma cell line FLO-1 (immortalised Barrett's oesophageal epithelial cells) and two Barrett’s cell lines (CPA (non-dysplastic metaplasia) and CPD (high-grade dysplastic metaplasia)) were used to challenge with organism as described by Mozaffari Namin et al ( 16 ). Briefly, FLO-1 was maintained in Dulbecco’s modified eagle medium (DMEM) (Sigma-Aldrich, Gillingham, UK) with 10% foetal calf serum (FCS) (Gibco-BRL life technologies, UK) and 1% penicillin/ treptomycin (Gibco-BRL, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another in vitro model study showed that the expression of tumor necrosis factor‐α and p53 was significantly reduced when two different Barrett's esophagus cell lines were co‐cultured with Bifidobacterium longum , and the inhibitory effect of probiotics might play a role in preventing the progression of Barrett's esophagus to adenocarcinoma . Our current preliminary investigation (unpublished) showed that the composition of the esophageal mucosal flora of the patients with esophageal squamous cell carcinoma ( n = 9) were significantly changed compared with controls ( n = 17).…”
Section: Discussionmentioning
confidence: 64%
“…22 Another in vitro model study showed that the expression of tumor necrosis factor-α and p53 was significantly reduced when two different Barrett's esophagus cell lines were co-cultured with Bifidobacterium longum, and the inhibitory effect of probiotics might play a role in preventing the progression of Barrett's esophagus to adenocarcinoma. 23 Our current preliminary investigation (unpublished) showed We found that esophageal mucosa contains many bacteria, and four strains of bacteria were significantly lower in patients with RE (Prevotella, Helicobacter, and Moraxella were reduced at the genus level, and Bacteroidetes was reduced at the phylum level). There was no significant difference between the two groups with respect to other genera.…”
Section: Discussionmentioning
confidence: 71%